2022
DOI: 10.1038/s41467-022-35099-3
|View full text |Cite
|
Sign up to set email alerts
|

Absolute excited state molecular geometries revealed by resonance Raman signals

Abstract: Ultrafast reactions activated by light absorption are governed by multidimensional excited-state (ES) potential energy surfaces (PESs), which describe how the molecular potential varies with the nuclear coordinates. ES PESs ad-hoc displaced with respect to the ground state can drive subtle structural rearrangements, accompanying molecular biological activity and regulating physical/chemical properties. Such displacements are encoded in the Franck-Condon overlap integrals, which in turn determine the resonant R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 70 publications
(78 reference statements)
0
9
0
Order By: Relevance
“…Furthermore, the pulse chirp can represent a convenient parameter to tune the beam temporal profile from an experimental point-of-view. By applying ultrashort chirped pulses, it can be found that the timescale of excitation is comparable to that of the electronic dephasing while the following adiabatic process relies on the chirp of the pulse inverting the population on a timescale much shorter than the dephasing time [40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the pulse chirp can represent a convenient parameter to tune the beam temporal profile from an experimental point-of-view. By applying ultrashort chirped pulses, it can be found that the timescale of excitation is comparable to that of the electronic dephasing while the following adiabatic process relies on the chirp of the pulse inverting the population on a timescale much shorter than the dephasing time [40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…6 In fact, thanks to the high level of accuracy that has been reached in the reproduction of experimental data in the condensed phase, it often provides a theoretical rationalization of many experimental findings, yielding truly synergistic investigations. [7][8][9] In fact, although many algorithms of increasing accuracy have been proposed and tested for systems in the gas phase, [10][11][12] the large majority of molecular spectra are routinely measured in the condensed phase, i.e. when chemical systems are dissolved in a solvent or other kinds of external environments (biological matrix, polymeric materials, crystal phase etc.).…”
Section: Introductionmentioning
confidence: 99%
“…Introduction of broadband (white-light) probe and using an array detector following spectral dispersion offers certain advantages in broadband ISRS over spontaneous Raman scattering and SRS as well as degenerate ISRS. [16] In broadband ISRS, [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] the third electric field (E 3 ) interaction involves a range of frequencies in broadband ISRS. Thus, several virtual levels are simultaneously accessed which may have different strength of coupling, leading to a variation of intensities of the signal with detection wavelengths which is manifested as islands in the contour plot of Raman shift at different detection wavelengths.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, several virtual levels are simultaneously accessed which may have different strength of coupling, leading to a variation of intensities of the signal with detection wavelengths which is manifested as islands in the contour plot of Raman shift at different detection wavelengths. [23,31] Broadband ISRS has been put to use to map the dynamics, [30] and quite recently the absolute geometries of molecules [33] in the electronic excited states. Further, in broadband ISRS, spectral association of coherent oscillations with population kinetics pertaining to ground-state bleach (GSB), stimulated emission (SE) and excited-state absorption (ESA) aids in isolation of signals since the GSB band projects vibrational dynamics in the ground electronic state while SE/ESA band maps dynamics in excited state.…”
Section: Introductionmentioning
confidence: 99%